1991
DOI: 10.1002/cbf.290090310
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chronic ethanol consumption on postnatal development of renal (Na + K)‐ATPase in the rat

Abstract: Renal (Na + K)-ATPase was studied to ascertain whether it follows the pattern of adaptation of membrane-bound enzymes that are inhibited by acute ethanol exposure and develop greater activity after chronic ethanol treatment. A colony of rats was given 20 per cent (v/v) ethanol as sole drinking solution throughout gestation, lactation and following weaning. (Na + K)-ATPase and ouabain-insensitive Ca(2+)-ATPase activities were determined; regional distribution of these enzymes was assessed in renal cortex and ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Several early reports by Rodrigo and colleagues revealed that chronic ethanol consumption in growing and adult rats causes an increase in (Na + K)-ATPase activity (Novoa and Rodrigo, 1989;Rodrigo et al, 1991). Such observations were supportive of other findings (Rodrigo et al, 1993a) of a positive sodium balance associated with a similar chronic ethanol consumption activity.…”
Section: Effects On Kidney Functionmentioning
confidence: 54%
“…Several early reports by Rodrigo and colleagues revealed that chronic ethanol consumption in growing and adult rats causes an increase in (Na + K)-ATPase activity (Novoa and Rodrigo, 1989;Rodrigo et al, 1991). Such observations were supportive of other findings (Rodrigo et al, 1993a) of a positive sodium balance associated with a similar chronic ethanol consumption activity.…”
Section: Effects On Kidney Functionmentioning
confidence: 54%
“…Specifically, protracted ethanol toxicity during chronic exposure cumulatively impacts other body systems that support brain development. For example, chronic alcohol exposure during gestation and lactation can negatively impact kidney function [57] and decrease fetal organ mass ratios [58]. For purposes of neural circuit examination these circumstances perturb the interpretation of causality, because the source of neurotoxicity can either be attributed to the direct interaction of alcohol, or alternatively as a byproduct of metabolic and/or systemic attrition from prolonged alcohol exposure (most likely a combination of these stressors).…”
Section: Animal Models Of Early Alcohol Exposurementioning
confidence: 99%
“…In fact, it is known that alcohol misuse may result in a generalized reduction in the reabsorptive ability of the proximal tubular cells (De Marchi et al, 1993). This hypothesis is supported by studies indicating that ethanol interferes with the carrier function of these cells by decreasing the Na + -K + -ATPase activity (Parenti et al, 1991;Rodrigo et al, 1991;Rothman et al, 1992). Furthermore, it is possible that the acetaldehyde, produced after oxidation of ethanol by alcohol dehydrogenase, may inhibit the activity of several enzymes in renal tubules (Gonzalez-Calvin et al, 1983;Rothman et al, 1992).…”
Section: Discussionmentioning
confidence: 93%